2011
DOI: 10.1159/000323456
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Modulation of the Inflammatory Bowel Response

Abstract: Crohn’s disease and ulcerative colitis represent distinct phenotypic forms of inflammatory bowel disease and continue to be a common cause of morbidity. The corticosteroids and the immunomodulatory drugs, which are the basis of treatment for the inflammatory bowel diseases, do not assure always satisfactory outcomes. Nutrition has been used in order to modify the inflammatory response of various chronic inflammatory diseases, including Crohn’s disease and ulcerative colitis. In the pathogenesis of inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 95 publications
(112 reference statements)
0
23
0
5
Order By: Relevance
“…Antioxidant vitamins and antioxidant-related trace metals in IBD mucosa. A number of reports are available on the level of b-carotene and vitamins A, C, and E, in the plasma/serum of patients with CD or UC (213,104). The large majority of these studies found a deficient blood content of antioxidant vitamins in IBD.…”
Section: Impairment Of Enzymatic Antioxidant Defense In Ibdmentioning
confidence: 99%
“…Antioxidant vitamins and antioxidant-related trace metals in IBD mucosa. A number of reports are available on the level of b-carotene and vitamins A, C, and E, in the plasma/serum of patients with CD or UC (213,104). The large majority of these studies found a deficient blood content of antioxidant vitamins in IBD.…”
Section: Impairment Of Enzymatic Antioxidant Defense In Ibdmentioning
confidence: 99%
“…Therefore, EN, if tolerated, represents the feeding route of choice [71]. In table 1, we demonstrate potential mechanisms of action of the nutritional agents [72,73]. …”
Section: Composition Of Enteral and Parenteral Nutrition Solutionsmentioning
confidence: 99%
“…Many studies have confirmed the important role of lipids in the diet to regulate inflammatory processes in different diseases, as they are the fundamental component of cell membranes, including those of lymphocytes and other immune cells, which orchestrate immune system responses (Ioannidis et al, 2011). Some studies have shown that high-fat diets have been associated with an imbalance between effector T cells and regulatory T cells and therefore with increased risk for UC what was confirmed in mouse models of experimental colitis.…”
Section: The Role Of Fats In Ulcerative Colitismentioning
confidence: 87%